Evaluation of Van A-B genes frequency in Vancomycin Resistant Enterococci spp., isolated from clinical samples of Imam Hossein Teaching Hospital in Tehran.: A molecular study of vancomycin-resistant-enterococci. - Javadi, Abdolreza; Behjoo, Bahareh; Forouhesh Tehrani , Homa; Vosough, Houman; Namadmal Torkashe, Kazem; Foroumand, Masoumeh; Barzegarian, Kavian (Novelty in Biomedicine, 2021)
Abstract Background: Antibiotic resistance is an important cause of treatment failure and re-infection in enterococci. In this study, the frequency of phenotype and genotype of Van A-B genes in Vancomycin resistant enterococcus isolated from a clinical sample of Imam Hossein Hospitals in Tehran was determined. Materials and Methods: In this descriptive cross-sectional study in 2018, a total of 76 vancomycin-resistant enterococci in Imam Hossein Hospitals in Tehran were evaluated, including those from blood, urine, sputum, and wound. The frequency of phenotype and genotype of Van A-B genes in them was determined by MIC Epsilometer test and Multiplex Real-time PCR. Results: The 160 isolates of enterococci collected from different hospital wards revealed that 76 (47%) enterococci were resistant by applying MIC E-test; interestingly, all VRE isolated showed high-level vancomycin resistance. The Real-time-PCR assay demonstrated vanA gene in 76 (100%) VRE isolates. Considering to controls no van B gene was detected in this assay. Based on bacterial phenotype tests, the results showed that 82% and 18% of the isolates were E. faecium and E. faecalis, respectively. Conclusion: Totally, it may be concluded that Van A gene is more accompanied by high-level Vancomycin Teicoplanin resistance in common enterococci species. The frequency of Vancomycin resistance entrocooci is increasing especially among ICU admitted patients. For effective treatment MIC test and Van A-B genotyping seem to be essential.